Studies in Armenian art : collected papers - Stone, Nira (University of Pennsylvania Armenian texts and studies, 2019)
Nira Stone (1938-2013) was a scholar of Armenian and Byzantine Art. Her broad and close acquaintance with the field of Armenian art history covered many fields of Armenian artistic creativity. Nira Stone made notable contributions to the study of Armenian manuscript painting, mosaics, and other forms of artistic expression. Of particular interests are her researches on this art in its historical and religious contexts, such as the study of apocryphal elements in Armenian Gospel iconography, the place of the mosaics of Jerusalem in the context of mosaics in Byzantine Palestine, and of the interplay between religious movements, such as hesychasm, and Armenian manuscript painting.